The permanent moral incapacity as grounds for presidential vacancy in the Political Constitution of Peru - Durand Herrera, Esmeralda (2024)
This article focuses on the subjective interpretation of presidential vacancy due to moral incapacity in the Peruvian Constitution, specifically in Article 113. It examines the historical evolution of this interpretation, moving from the initial conception of mental incapacity towards an ethical approach to individual behavior. The analysis focuses on recent cases, such as the attempts to remove Pedro Pablo Kuczynski in 2018 and the vacancy of Martín Vizcarra in 2020, highlighting the threat of discretionary use of this cause for political purposes. The article seeks to propose solutions to prevent arbitrary interpretations through legislative and constitutional reforms, supported by a casuistic and doctrinal analysis. It emphasizes the need to clarify and objectify the criteria of moral incapacity, avoiding its manipulation for political motivations. The research aims to contribute to institutional stability, ensuring that presidential vacancy adheres to solid constitutional principles and does not become a discretionary tool in the hands of partisan interests.